The rapidly changing treatment landscape of first-line advanced urothelial cancer (aUC) or metastatic urothelial cancer (mUC) - Minira Aslanova; Eun-Mi Yu; Jeanny B. Aragon-Ching (Open Exploration Publishing Inc., 2024)
The landscape of treatment for first-line therapy in advanced urothelial cancer (aUC) and metastatic urothelial cancer (mUC) has rapidly changed in the last year alone. Maintenance avelumab remains a viable treatment option for many patients across the globe for those who have responded or have achieved stable disease after platinum-based chemotherapy. However, the recent FDA approvals based on EV-302 for enfortumab vedotin (EV) and pembrolizumab, as well as CheckMate-904 with gemcitabine and cisplatin with nivolumab (GC+N) followed by maintenance nivolumab have left clinicians with the complicated decision of determining which regimen is most appropriate for their individual patients with untreated aUC. This commentary highlights the key trials that have set the standard-of-care for front-line aUC treatment and suggestions for choosing different regimens for the appropriate patient.